(3GdhLjR aj GdbGfhf GdEOGQj GdSYhOj (B/s - (3GdeUQj, UHGM eUWai MSfs ((3GdbGgQI (B:s (3OGQ GdcJGH GdLGeYj ddfTQ hGdJhRjY,s, 2019)
(3jJfGhd cJGH (B((3GdhLjR aj GdbGfhf GdEOGQj GdSYhOj(B) (3hGdPj bGe HJCdjag (B((3UHGM GdeUQj(B) (3aj MhGdj (B(449) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbGfhf GdEOGQj GdSYhOj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3ebOeI, GdHGH GdChd (B: (3eGgjI GdbGfhf GdEOGQj, hjTed GdaUd GdChd (B: (3JMOjO eaghe GdbGfhf GdEOGQj, GdaUd GdKGfj (B: (3fWGb GdbGfhf GdEOGQj hCTNGUg, GdaUd GdKGdK (B: (3fXGe GddGeQcRjI GdEOGQjI hJWHjbGJg aj GdeedcI GdYQHjI GdSYhOjI(B... (3EdN(B.s
(3fSNI efbMI heMOKI habG dCMOK GdCfXeI GdEOGQjI(B.s
(3ebQQGJ OQGSjI (B2025-2026.s
(3HHdjhLQGajI (B: (3UaMI (B435-440.s
Keywords: (3GdbGfhf GdEOGQjs -- (3GdSYhOjIs; (3GdbVGA GdEOGQjs -- (3GdSYhOjIs